(untitled) (Indian Journal of Animal Production and Management, 2024)
To compare the effect of different floor space allowances on physiological status of pigs, 36 crossbred (Landrace x Desi) barrows were reared with 3 different floor space allowances n = 4(group size) x 3(replications) = 12 each. Group TIS (control) had floor space allowance (0.9, 1.35 and 1.8 m2/pig during weaner, grower and finisher stage) as per Indian Standards (IS: 3916-1966), while T2/3 and T1/2 treatment groups had 33% and 50% reduced floor space allocation with fixed small (n=4) group size throughout the experiment. Skin lesion score, blood parameters and back fat thickness (BFT) of pigs were estimated. Mean skin lesion score of head and ears (weaner, P<0.05) was lower in TIS group than other groups, and body regions (finisher, P<0.05) was lower in TIS than T1/2 group, whereas, lesion score for other body parts and growth stages did not differ among the groups. Plasma cortisol concentration was higher (P<0.05) in T1/2 group than other groups (grower) and TIS group (finisher). BFT of pigs did not differ statistically among the groups. It is concluded that suitable floor space allowance in Indian conditions should lie between T2/3 and T1/2 group for crossbred pigs.